2022
DOI: 10.1177/15593258211073412
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical, Antioxidant, Toxicological, and Pharmaceutical Evaluation of Polyherbal Formulation: Irochel

Abstract: Background and Purpose: Irochel is a polyherbal formulation, comprises ethanolic extracts of Emblica officinalis, Cucurbita pepo L, Triticum aestivum, Fagonia cretica, Momordica charantia, and Tribulus terristris. It is prepared for the management of iron overload in transfusion-dependent thalassemia patients in which non-transfusion binds iron-produced reactive oxygen species ROS that causes severe damages to the organs leads to death. Research Study: In this study, phytochemical, antioxidant-DPPH assay, cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…These formulations have been traditionally used in various cultures for the management of liver diseases, and recent studies have shown promising results in their hepatoprotective effects, with negligible side effects (Iroanya, Adebesin & Okpuzor 2014;Padmanabhan & Jangle 2014;Shetty et al 2018Shetty et al , 2020. They have been found to contain a variety of bioactive compounds such as flavonoids, alkaloids and terpenoids, which exhibit various pharmacological activities such as antioxidant, antiinflammatory and hepatoprotective effects (Ghayas, Hannan & Rizwani 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These formulations have been traditionally used in various cultures for the management of liver diseases, and recent studies have shown promising results in their hepatoprotective effects, with negligible side effects (Iroanya, Adebesin & Okpuzor 2014;Padmanabhan & Jangle 2014;Shetty et al 2018Shetty et al , 2020. They have been found to contain a variety of bioactive compounds such as flavonoids, alkaloids and terpenoids, which exhibit various pharmacological activities such as antioxidant, antiinflammatory and hepatoprotective effects (Ghayas, Hannan & Rizwani 2022).…”
Section: Introductionmentioning
confidence: 99%